A Case of Peritoneal-Pelvic Tuberculosis With Elevated CA-125; An Enigma as Ovarian Cancer - Oli, Prakash Raj; Malla, Rosy Vaidya; Karmacharya, Kavita (Medical Journal of Shree Birendra Hospital, 2019)
Peritoneal-pelvic tuberculosis is a rare form of extrapulmonary-TB mainly affecting women of 20-40 years, especially in TB endemic countries. It classically presents with abdominal pain, menstrual irregularities, adnexal mass, and elevated serum CA-125 level, creating confusion with genital malignancy, especially ovarian one leading to difficulty in its management and often leads to devastating surgeries. Here's a case of peritoneal-pelvic TB, a young lady with abdominal pain, radiologic associates and adnexal mass, and elevated serum CA-125 level is presented. So, it should always be one of the differential diagnosis of ovarian cancer especially among young women in TB endemic countries.